Pengaturan Hukum Penggunaan Spyware oleh Kepolisian Siber Dalam Pengawasan Digital - Putra, Akbar Tristanto; Simangusong, Frans (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of information technology in the digital era has encouraged law enforcement officials, particularly cyber police, to adopt increasingly sophisticated digital surveillance tools to detect, analyze, and prevent complex and rapidly changing cybercrimes. One instrument often associated with law enforcement intelligence functions is the use of malicious software (spyware) capable of covertly accessing information and collecting sensitive data from target devices. Although spyware is operationally effective in intelligence activities, its use raises fundamental issues related to legality, limits of authority, and protection of citizens' privacy rights. In the Indonesian context, the police's authority to conduct digital surveillance is based on Law No. 2 of 2002 concerning the Indonesian National Police and Law No. 17 of 2011 concerning State Intelligence, but neither regulation specifically regulates the mechanisms for spyware use. On the other hand, the Electronic Information and Transactions Law (UU ITE) and the Personal Data Protection Law impose strict restrictions on illegal access, interception, and processing of personal data without a valid legal basis. Therefore, this study examines the urgency of comprehensive legal regulations for the use of spyware by cyber police to ensure a balance between effective law enforcement and human rights protection. The study's findings indicate that specific regulations are needed to prevent abuse of authority, ensure accountability, and ensure that digital surveillance is conducted based on the principles of legality, proportionality, and transparency within a democratic, rule-of-law framework.